Perancangan Sistem Penyewaan Sepeda Listrik Berbasis Mobile dengan Pendekatan UML - Zatin Niqotaini; Dwi Vernanda; Henki Bayu Seta; Yanti Andriyani (Fakultas Ilmu Komputer, 2025)
Innovation in transportation, such as online transportation booking applications and electric vehicles are phenomena caused by the development of information technology. But, the likes of traffic safety and complex transportation system integration are some obstacles that still need to be addressed. This research aims to design a Mobile-Based Electric Bicycle Rental System using Unified Modeling Language (UML) in order to increase efficiency and convenience. A Qualitative Research Method is used to analyze the Business Process. The System Analysis stage involves identification, determining requirements, and systematic study to ensure design compliance or suitability. The System Designing stage covers creating structured UML Model, Database Design, determining Table Structure, and developing a User Interface. This study’s result presents a comprehensive design of the Electric Bicycle Rental System, reflected by well-structured UML Diagrams, efficient Database Design and an intuitive User Interface. This System is expected to be an innovative solution to conquer efficiency and convenience hurdles in renting an Electric Bicycle.